Circadian Profile of Salivary Melatonin Secretion in Hypoxic Ischemic Encephalopathy - Łukasz Kapek; Justyna Paprocka; Marek Kijonka; Maria Zych; Ewa Emich-Widera; Beata Rzepka-Migut; Damian Borys; Ilona Kaczmarczyk-Sedlak; Maria Sokół (International Journal of Endocrinology)
Purpose. In the present study, the salivary melatonin secretion in the hypoxic ischemic encephalopathy (HIE) children was measured. The logit model was fitted to the data to obtain the salivary dim light melatonin onsets (DLMOs), and the results were compared with the values estimated from the classic threshold method with a linear interpolation and those previously published for the blood measurements. Materials and Methods. 9 patients suffering from HIE aged from 65 to 80 months were included in the study. The melatonin levels were assessed by a radioimmunoassay (RIA). The diurnal melatonin secretion was estimated using a nonlinear least squares method. Student’s t-test and the Mann–Whitney U test were used for the comparisons of the obtained parameters. Results. The circadian profiles of the melatonin secretion for both calculation methods do not differ statistically. The DLMO parameters obtained in the blood and saliva samples in children with hypoxic ischemic encephalopathy were similar.